A rare case of fungal keratitis: diagnosis and management. Issue 5 (8th October 2015) - McElnea, Elizabeth; Farrell, Stephen; Lynch, Breda; Bishop, Ken; Mullen, Dorinda; Borman, Andrew; Higgins, Gareth
Abstract : Introduction: We report a case of keratitis caused by a member of the Phoma species of fungi. Case presentation: A 59-year-old contact lens wearer developed a non-healing corneal ulcer. Microbiological culture and subsequent PCR analysis were performed using samples obtained from corneal scraping. A fungus, phenotypically identified as a member of the Phoma species of fungi, was cultured. PCR from infected tissue confirmed the diagnosis. Conclusion: Although rarely pathogenic to humans, members of the ubiquitous Phoma species of fungi can occasionally cause keratitis. Corneal microtrauma associated with contact lens wear is probably important in precipitating such infections.